Research on key technologies of direct-to-handset under satellite-terrestrial integrated network - LIU Hui; YE Yang; DING Zhidong; LIU Xianghua; ZHU Ziyuan; ZHOU Jing (Dianxin kexue)
Nowadays, the demand of consumers and industrial users for satellite-terrestrial integrated communications is evolving to achieve seamless coverage and anytime, anywhere access, and the integration of satellite and terrestrial communication capabilities will be the development direction of future mobile phones. The application scenarios for direct-to-handset connectivity, domestic and international development paths, and related technical solutions were introduced. Subsequently, the network architecture and key technology for realizing direct-to-handset connectivity with respect to the 3GPP NTN standard scheme were analyzed. The requirements and potential improvement schemes for multi-mode terminals in satellite communication scenarios in terms of integrated design, antenna capabilities, voice capabilities and power saving, were also identified. Finally, by exploring the key regulatory challenges (e.g. radio-frequency spectrum) related to direct-to-handset communications, feasible pathways for the future development of satellite-terrestrial integrated terminals were provided.